Analysis of gamete membrane dynamics during double fertilization of Arabidopsis - Igawa, Tomoko (Springer Japan, 2012)
Angiosperms have a unique sexual reproduction system called “double fertilization.” One sperm cell fertilizes the egg and another sperm cell fertilizes the central cell. To date, plant gamete membrane dynamics during fertilization has been poorly understood. To analyze this unrevealed gamete subcellular behavior, live cell imaging analyses of Arabidopsis double fertilization were performed. We produced female gamete membrane marker lines in which fluorescent proteins conjugated with PIP2a finely visualized egg cell and central cell surfaces. Using those lines together with a sperm cell membrane marker line expressing GCS1-GFP, the double fertilization process was observed. As a result, after gamete fusion, putative sperm plasma membrane GFP signals were occasionally detected on the egg cell surface adjacent to the central cell. In addition, time-lapse imaging revealed that GCS1-GFP signals entered both the egg cell and the central cell in parallel with the sperm cell movement toward the female gametes during double fertilization. These findings suggested that the gamete fusion process based on membrane dynamics was composed of (1) plasma membrane fusion on male and female gamete surfaces, (2) entry of sperm internal membrane components into the female gametes, and (3) plasmogamy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10265-012-0528-0) contains supplementary material, which is available to authorized users.